Molecular and electronic structures of donor-functionalized dysprosium pentadienyl complexes12. Issue 16 (23rd March 2015) - Day, Benjamin M.; Chilton, Nicholas F.; Layfield, Richard A.
Abstract : The molecular structures of two dysprosium complexes of donor-functionalized pentadienyl ligands are described. Electronic structure calculations reveal that the W-shaped pentadienyl ligand strongly influences the orientation of the main magnetic axis of the ground Kramers doublets in both complexes. Abstract : Two dysprosium complexes, [(C5 H4 Me)2 Dy(L 1 )] (3 ) and [(L 1 )Dy(μ-Cl)3 {Li(tmeda)}]2 (4 ), with amino-functionalized pentadienyl ligands L 1 are described. Crystallographic studies of3 and4 show that the pendant amino group influences the pentadienyl conformation and the ligand hapticity. Electronic structure calculations reveal that L 1 has a strong influence on the orientation of the main magnetic axis of the ground Kramers doublets in3 and4 .